TANTANGAN DAN STRATEGI DALAM PROSES EVALUASI PEMBELAJARAN : PANDANGAN TERKINI DAN PROSPEK DI MASA DEPAN - Muhammad Ridho Aliffiansyah; Ismail; Nurhilaliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
As an important component of the educational process, learning evaluation is fraught with complex difficulties. Difficulties and approaches in learning evaluation are discussed in this article along with potential developments in the future. These difficulties include the complexity of comprehensively evaluating student progress, the need for assessments to be inclusive, and the incorporation of technology into evaluation tools. Various approaches are needed to overcome this problem, such as a focus on formative assessment, the creation of customizable assessment instruments, and the application of technology to increase the effectiveness and efficiency of evaluation. Current perspectives emphasize the need for comprehensive strategies that respond to students' needs and consider their social, emotional, and general well-being. This approach is expected to encourage continuous learning, increase student achievement, and produce learning assessments that are more inclusive, flexible, and successful. The method used in this research is library research, by examining primary and secondary sources.